CAUSES OF CHILDREN COMMITTING THEFT CRIMES (Case Study of the Ngawi District Attorney's Office in 2022) - Agustin Dwi Ria Mahardika; Rehnalemken Ginting (Pelopor Publikasi Akademika, 2023)
In the future, the child plays an important role in shaping the history, country and way of life of a country. In other words, children are the next generation of the nation. However, the potential for criminal behavior is also inherent in children. One of them is through theft. The factors that underlie children committing theft include family, environment, and even self. This study aims to determine and examine the factors that cause children to commit theft, as well as the efforts made to prevent this occurrence and law enforcement. This legal research uses descriptive analysis techniques by combining sociological or empirical approaches. Based on the results of the study, the main factors that encourage young people to commit theft in the Ngawi region are family, education, and economic factors. Poor education, weak economy, and a less harmonious family environment due to family conditions that are no longer intact due to divorce or death of parents, become additional factors in themselves. As a result, children lose positive role models on how to live their lives. To overcome this, efforts are needed to handle it as early as possible with various approaches and patterns of prevention, repressive, and curative handling.